Chaetopterus antarcticus (Polychaeta: Chaetopteridae) in Argentinian shelf scallop beds: from infaunal to epifaunal life habits - Bremec, Claudia Silvia; Schejter, Laura (Revista de Biología Tropical)
The shelf-break frontal area in the Argentine Sea, between 37º S and 40º S, ischaracterized by high frequency and abundance of the parchment worm Chaetopterus antarcticus Kinberg, 1866 associated to Zygochlamys patagonica scallop beds. This polychaete was usually collected within its U tubes, typical of infaunal habit. During 2007, a surprising massive settlement of worms on scallops was observed. Objective: Our objectives is to report the variability of life habits of C. antarcticus in scallop grounds distributed between 37º S and 40º S in Argentinean waters. Methods: The presence of the parchment tube worms on Z. patagonica was analyzed in 892 scallops coming from three samples collected in September (previously obtained for other purposes) and November 2007 and April 2008, between 99-106 m depth in Management Unit B (16.186 km2, 38º S - 39º 52? S). Polychaetes were identified and quantified on both valves. In addition, bothepibiont and infaunal worms were registered through time. The settlement of C. antarcticus on scallops was monitored during the period 2007-2015 and the presence of free tubes, both empty and inhabited by worms, were registered during the period 2008-2015 from a total of 374 representative subsamples (10 l) collected with trawling tools between 37º S and 40º S. Results: Scallops collected in 2007 and 2008 showed that 468 (> 50 %) specimens were encrusted; in 66 % (311 specimens) of them C. antarcticus was settled. The temporal analysis showed that the spatial distribution of epibiotic worms decreased in 2009, 2010 and 2012, with its total absence in 2013, 2014 and 2015 in the study area. During the period 2007 - 2015, infaunal worms were registered throughout thearea, collected in part of the locations monitored. Conclusions: The variability of life habits of C. antarcticus was not commonly registered previously in the study area; epibiotic behavior could be the result of intensive soft sediment disturbance due to trawling and hence, the selection of other available primary settlement ...